Perlindungan Hukum Pasien dalam Pelayanan Kesehatan: Studi di IGD Puskesmas Sape Kabupaten Bima - Suhardiyanto, Rifki; Dewi, Anies Prima; Syahrial Haq, Hilman; Sahrul (Yayasan Pendidikan Kardin Assidiq, 2025)
Background: Indonesia has pressing issues regarding Quality health services and patient protection. This study investigates the legal protections available to patients who receive inadequate services, as provided by Law Number 8 of 1999 concerning Consumer Protection. It focuses on implementing health services in the emergency room at the Sape Community Health Center, Bima Regency. Objective: The primary aim of this study is to assess the legal protections for patients confronting substandard health services and to evaluate the effectiveness of these services in the emergency room. Method: The research employs a combination of normative and empirical legal methods. Data was gathered through document analysis, interviews, observations, and literature reviews, with qualitative descriptive techniques used for data analysis. Results: The findings reveal that Law Number 8 of 1999 offers significant protections for patients experiencing poor health services, including the right to clear information, safe medical procedures, and the ability to lodge negligence claims. However, the registration process, particularly for BPJS patients, is cumbersome, even though initial medical actions and observations are handled appropriately. Conclusion and Recommendations: While Law No. 8 of 1999 safeguards patient rights, it is recommended that the Sape Health Center streamline the registration process for BPJS patients and enhance the promotion of patient rights as stipulated under the Consumer Protection Law.